2022
DOI: 10.3390/diagnostics12061325
|View full text |Cite
|
Sign up to set email alerts
|

Epidermolysis Bullosa—A Different Genetic Approach in Correlation with Genetic Heterogeneity

Abstract: Epidermolysis bullosa is a heterogeneous group of rare genetic disorders characterized by mucocutaneous fragility and blister formation after minor friction or trauma. There are four major epidermolysis bullosa types based on the ultrastructural level of tissue cleavage: simplex, junctional, dystrophic, and Kindler epidermolysis bullosa. They are caused by mutations in genes that encode the proteins that are part of the hemidesmosomes and focal adhesion complex. Some of these disorders can be associated with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 133 publications
(223 reference statements)
0
4
0
Order By: Relevance
“…Mutational analysis for the enamel defect revealed a recurrent frameshift pathogenic variant in the LAMB3 gene. This gene has been associated with intermediate and severe junctional epidermolysis bullosa (JEB1A and JEB1B, OMIM #226650 and #226700) in autosomal recessive inheritance [12]. Later, it was identified that some specific heterozygous mutations cause AI, Type IA (autosomal dominant hypoplastic AI, OMIM #104530) [13,14].…”
Section: Familymentioning
confidence: 99%
“…Mutational analysis for the enamel defect revealed a recurrent frameshift pathogenic variant in the LAMB3 gene. This gene has been associated with intermediate and severe junctional epidermolysis bullosa (JEB1A and JEB1B, OMIM #226650 and #226700) in autosomal recessive inheritance [12]. Later, it was identified that some specific heterozygous mutations cause AI, Type IA (autosomal dominant hypoplastic AI, OMIM #104530) [13,14].…”
Section: Familymentioning
confidence: 99%
“…EB is characterised by the formation of numerous blisters on the skin as a result of minor mechanical trauma. Individual subtypes can produce symptoms such as nail dystrophy, pigmentation abnormalities, alopecia or even cardiomyopathy [40]. It has been shown that the use of preparations containing betulin, due to its anti-inflammatory and antibacterial properties, can be helpful in eliminating skin damage caused by EB [16,41].…”
Section: Use Of Betulin and Betulinic Acid In The Treatment Of Skin D...mentioning
confidence: 99%
“…Occasionally EBS can have a fatal outcome. The onset of EBS varies based on its subtype, typically manifesting at birth or during infancy ( 3 ). For accurate classification of EBS, it is imperative to consider the specific clinical features alongside molecular findings.…”
Section: Introductionmentioning
confidence: 99%